Analisis Kemampuan Thinking Ahead dalam Penyusunan Road Map Reformasi Birokrasi Pemerintah Daerah (Studi Kasus di Pemerintah Kabupaten Malang) - Ristanti, Rahmadina Fitria (Jurnal Ilmiah Administrasi Publik, 2021)
Bureaucratic reform is one of the policies to improve the existing bureaucratic conditions and allows the bureaucracy to adapt to environmental changes. The ultimate goal of bureaucratic reform in Indonesia is dynamic governance. Based on Neo and Chen’s dynamic governance frame work, one of the dynamic capabilities to achieve dynamic governance is thinking ahead. In bureaucratic reform, the ability to think ahead can be applied in roadmapping process of bureaucratic reform in order to produce adaptive policies. This study aims to analyze the capability of thinking ahead in roadmapping process of bureaucratic reform in Malang Regency Government and the factors that affect it. The results showed that the Malang Regency Government in roadmaping process of bureaucratic reform had not implemented the thinking ahead; and factor of able people and agille processes affect on the application of the thinking ahead.